PEMBERIAN TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT TERFORMULASI TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS BAWANG MERAH (Allium ascalonicum L.) DI LAHAN GAMBUT - Dewi Marlina Susanti; - Herman; Fifi Puspita (LPPM Universitas Muhammadiyah Riau, 2017)
This study aimed to get to know the effect of different doses formulated Trichokompos doses on the growth and production of onion varieties in peat area, as well as to get a dose of Trichokompos formulated and the best interaction on several onion varieties. Research using split plot design draft with 12 combination and each treatment was repeated 3 times, analyzed in the laboratory and analysis of variance. The main plot treatments consisted of: (V1): Varieties Bauji, (V2): Varieties Maja Cipanas, (V3): Varieties Bima Brebes. Treatment subplot, consists of 4 levels, namely: T1: (5 ton / ha), T2 (10 tons / ha), T3 (15 ton / ha) and T4 (20 ton / ha). The data obtained were statistically analyzed using analysis of variance (ANOVA) followed by HSD test at 5% level. The results of the research showed that, the provision of oil palm empty bunches Trichokompos formulated doses of 10 ton / ha and a dose of 20 ton / ha on the varieties Bauji can increase the content of chlorophyll by 78.64% and K nutrient uptake value of 2.46 mg / plant. Provision of Oil Palm Empty Fruit Bunch Trichokompos formulated doses of 10 ton / ha on Maja Cipanas varieties could increase plant height of 24.93 cm and a dose of 5 tonnes / ha can increase the diameter of the bulbs by 24.70% and the provision of oil palm empty bunches Trichokompos formulated doses of 5, 10 , 15 and 20 ton / ha on Bima Brebes varieties can increase the number of tillers, the number of bulbs, tubers fresh weight, fresh weight of the plants, the rate of photosynthesis, transpiration rate, stomata conductivity, CO2 concentration, the value of N uptake and nutrient uptake value P. Increasing doses of oil palm empty bunches Trichokompos formulated from 5 to 20 ton / ha on the varieties Bauji, Maja Cipanas and Bima Brebes not affect all parameters observed.